Efficient Inhibition of Telomerase by Nickel–Salophen Complexes. (11th May 2016) - Lecarme, Laureline; Prado, Enora; De Rache, Aurore; Nicolau‐Travers, Marie‐Laure; Gellon, Gisèle; Dejeu, Jérôme; Lavergne, Thomas; Jamet, Hélène; Gomez, Dennis; Mergny, Jean‐Louis; Defrancq, Eric; Jarjayes, Olivier; et al.
Abstract: Four nickel(II)–salophen complexes containing alkyl‐imidazolium chains connected at the ortho or meta positions were prepared: N, N ′‐bis(2‐hydroxy‐4‐methyl‐3 H ‐imidazol‐1‐iumbenzylideneamino)phenylenediamine (1 ), N, N ′‐bis(2‐hydroxy‐3‐methyl‐3 H ‐imidazol‐1‐iumbenzylideneamino)phenylenediamine (2 ), N, N ′‐bis(2‐hydroxy‐3‐methyl‐3 H ‐imidazol‐1‐iumbenzylideneamino)methyl‐3 H ‐imidazol‐1‐iumphenylenediamine (3 ), and N, N ′‐bis(2‐hydroxy‐4‐methyl‐3 H ‐imidazol‐1‐iumbenzylideneamino)methyl‐3 H ‐imidazol‐1‐iumphenylenediamine (4 ). They protect G‐quadruplex DNA (G4 ‐DNA) against thermal denaturation and show K A values in the range of 7.4×10 5 to 4×10 7 m −1 for G4 ‐DNA models. Complex4 exhibits an IC50 value of 70 nm for telomerase inhibition. Abstract : Four for the quad : Four polycationic nickel–salophen complexes were found to interact strongly and selectively with quadruplex DNA. One complex exhibits a remarkable IC50 of 70 nm for telomerase inhibition as determined by TRAP‐G4 assay. The results of this study provide new perspectives for the design of modular G‐quadruplex ligands.